Factors influencing consumer intention to purchase halal food among Muslims in Thailand - Wacharajirasophon, Miss Usanee (Kuliyyah of Economics and Management Science, International Islamic University Malaysia, 2016)
With the rising global demand for Halal food, more countries have emerged to serve this potential market, including non-Muslim countries. Thailand is one of them which plans to be a Halal food hub with the aim to become a major Halal food exporter regardless of the relevant Halal issues in the country. The demand for Halal food in the Thai market itself has also increased recently and continue to have an upward trend. If it is this reason, an investigation of Muslim consumers' consumption behavior becomes an interesting subject. Many researches have been conducted to try to understand factors that influence Muslim consumers in their choice of purchase. Previous researches support that behaviors are greatly influenced by intention while many researches on consumer intention to purchase Halal food have been conducted in the Muslim countries. This study emphases consumer intention to purchase Halal food in non-Muslim country, Thailand. The data were collected by self-administered questionnaires from respondents in the Songkhla province. The proposed research model is based on the Theory of Planned Behavior (TPB) and extended to include certain relevant factors to investigate the association among attitude, subjective norm, perceived behavioral control, religiosity, and trust on consumer intention to purchase Halal food. Factor analysis was conducted to ensure the validity of the research instrument. Then, the Partial Least Square (PLS) was utilized to test the hypotheses. The findings indicate that the extended Theory of Planned Behavior (TPB) is applicable to explain consumer intention to purchase Halal food in Thailand. Four out of five propositions had significant support in which attitude, subjective norm, religiosity, and trust predict consumer intention to purchase Halal food among Thai Muslim consumers, though perceived behavioral control did not show a significant influence on consumer intention. The findings of this research provide valuable implication for Marketing Managers and also contribute to the academic perspective by enlarging the body of knowledge.